Unleashing the Central Bank Digital Currency Revolution and its Impact on Exchange Rate: A Monetary Approach Synthesis - Akhmad Syakir Kurnia; Muhammad Adnan Assidiq (ETIKONOMI, 2024)
Research Originality: The introduction of CBDC by the Central Bank of Indonesia has increased the intensity of news about CBDC. Besides aiming to introduce the future direction of the payment system, the news potentially causes uncertainty and speculation in the market, which may impact the rupiah exchange rate.Research Objectives: This research analyzes the impact of CBDC news on the rupiah exchange rate, synthesizing a sticky price version of the monetary approach to the exchange rate. Research Methods: A CBDC News Index is constructed based on a compilation of news data from major online media between 2018 and 2023. The structural VAR (SVAR) method is thenemployed to investigate the impact of CBDC news on the exchange rate dynamic.Empirical Results: The results suggest a trend consistent with the hypothesis, indicating that news about CBDC may lead to pressure on the domestic currency, resulting in depreciation. However, the impact is not statistically convincing as the coefficient is not statistically different from zero. The monetary approach synthesis findings suggest that raising the policy rate is likely efficacious in counteracting the pressure of domestic currency depreciation. Meanwhile, other monetary approach variables exhibit anomalies related to exchange rate dynamics.Implications: As the central bank plans to implement a Central Bank Digital Currency (CBDC), it must carefully control the dissemination of information about what the CBDC will entail and how it will be rolled out. CBDC blueprint and official disclosure help reduce uncertainty and speculation about implementing CBDC.JEL Classification: D80, E58, F31How to Cite:Kurnia, A. S. & Assidiq, M. A. (2024). Unleashing the Central Bank Digital Currency Revolution and Its Impact on Exchange Rate: A Monetary Approach Synthesis. Etikonomi, 23(2), 271-286. https://doi.org/10.15408/etk.v23i2.37788